1993
DOI: 10.1002/pd.1970130306
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in maternal serum human chorionic gonadotropin and unconjugated oestriol levels

Abstract: We assayed maternal serum samples from 134 black and 268 white women from 16 to 18 weeks of gestation for intact human chorionic gonadotropin (hCG), and unconjugated oestriol (uE3). Serum from women with high (> or = 2.5 MOMs) or low (risk for Down syndrome > or = 1/365) maternal serum alpha-fetoprotein (MSAFP) levels were excluded. After correcting for maternal weight, we found that median hCG levels were 16 per cent higher in black women but uE3 levels were not significantly different. These results confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Several studies have reported racial differences in prenatal screening marker medians (Crandall et al, 1983;Canick et al, 1990;Bradley et al, 1991;Kulch et al, 1993;O'Brien et al, 1993), and investigators have reported differences between commercially available radioimmunoassay kits (Kallestad AFP/Ob Radioimmunoassay, Chaska, Minnesota, U.S.A.; Serono MAIAclone Immunoradiometric hCG assay, BIODATA, Milano, Italy; Unconjugated Estriol Radioimmunoassay, Diagnostic Systems Laboratory, Webster, Texas, U.S.A.). Additional information collected included date of birth, maternal age at delivery, gestational age, maternal weight, number of fetuses, insulindependent diabetes mellitus (IDDM) status, and any family history of DS or ONTD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported racial differences in prenatal screening marker medians (Crandall et al, 1983;Canick et al, 1990;Bradley et al, 1991;Kulch et al, 1993;O'Brien et al, 1993), and investigators have reported differences between commercially available radioimmunoassay kits (Kallestad AFP/Ob Radioimmunoassay, Chaska, Minnesota, U.S.A.; Serono MAIAclone Immunoradiometric hCG assay, BIODATA, Milano, Italy; Unconjugated Estriol Radioimmunoassay, Diagnostic Systems Laboratory, Webster, Texas, U.S.A.). Additional information collected included date of birth, maternal age at delivery, gestational age, maternal weight, number of fetuses, insulindependent diabetes mellitus (IDDM) status, and any family history of DS or ONTD.…”
Section: Introductionmentioning
confidence: 99%
“…Such adjustment increases detec tion while decreasing the false-positive rate. The effect is less pronounced in Down syndrome screening, although higher hCG levels have also been reported in AfricanAmericans when compared with Caucasians [14,15]. A few studies have looked at Asian populations with similar findings of higher mid-trimester levels of hCG [16][17][18], O'Brien et al [ 17,18] looked at serum screening in a New York metropolitan area population, and found a consis tent pattern of analyte differences across all gestational ages, with highest values for all three analytes in Asians.…”
Section: Discussionmentioning
confidence: 96%
“…Most computer programs for the analysis of risk allow for this factor. Levels of hCG tend to be higher in Asian women [101] and black women [79,135], but because of some conflicting evidence corrections are usually not made for these factors. After 18 weeks gestation hCG levels are higher in the presence of a female fetus [71,81].…”
Section: Should Tests Be Repeated?mentioning
confidence: 99%